2019
DOI: 10.5897/ajar2018.13556
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Trichoderma asperellum UFT 201 as plant growth promoter in soybean

Abstract: Filamentous fungi of the genus Trichoderma are known for their activity as plant growth promoters. The objective of this work was to evaluate the efficiency of the Trichoderma asperellum UFT 201 strain as a plant growth promoter in soybean. The ability of phosphate solubilization, indole acetic acid synthesis and the effect on soybean plant growth under greenhouse conditions were evaluated in four experiments. In vitro and in vivo analyzes were performed. Plant biomass characteristics such as shoot dry mass (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Trichoderma inoculation in soybean, like Chagas et al (2017a), Gonçalves et al (2018) and Chagas Junior et al (2019a, b) who concluded that Trichoderma acts as a promoter of vegetable growth positively affecting biomass and soybean productivity.…”
Section: Some Authors Have Reported Positive Results Withmentioning
confidence: 98%
“…Trichoderma inoculation in soybean, like Chagas et al (2017a), Gonçalves et al (2018) and Chagas Junior et al (2019a, b) who concluded that Trichoderma acts as a promoter of vegetable growth positively affecting biomass and soybean productivity.…”
Section: Some Authors Have Reported Positive Results Withmentioning
confidence: 98%
“…Trichoderma priming enhanced the shoot length, root length, total leaf area, shoot dry biomass and root dry biomass in wheat (Figure 2). Trichodermainduced enhancement in aerial and radicular growth has been reported for a wide range of crop species (Singh et al, 2016;Aloisio et al, 2019;Moya et al, 2020). Such effects may be due to the capability of Trichoderma to increase nutrient availability, phosphate solubilisation and production of growth hormones such as Indole ascetic acid (IAA) in primed wheat (Singh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, a yellow halo zone around the fungal colony indicated phosphate solubilizing ability. The solubilization zone and colony diameters were measured and calculated using the equation below to indicate the solubilization efficiency (Pande et al, 2017;Aloisio et al, 2019). SE = (Solubilization diameter)/(Growth diameter) ×100.…”
Section: Phosphate Solubilization Efficacy Of Trichoderma Asperellummentioning
confidence: 99%